Temporal bone dysplasia in Coffin-Siris syndrome. Issue 1 (18th January 2021) - Wauchope, Jessica; Leonard, Colin; McKinstry, Steven; Trimble, Keith
Abstract : We report a child, diagnosed with Coffin-Siris syndrome (CSS), with chronic right otorrhoea. CT and DR-MRI were performed to further investigate, diagnose and determine relevant surgical anatomy. CT temporal bones assessment was performed, and the measurements compared with previously published data for normal temporal bone anatomy. These comparisons highlighted various differences which were not initially expected; it showed that there were multiple inner ear abnormalities in addition to middle ear disease. This case highlights the importance of considering temporal bone abnormalities in all children with CSS or any dysmorphia, when they may require mastoid procedures. Reviewing the management of this case provides relevant learning opportunities for both primary, secondary and tertiary care institutions.